Pembuatan Sistem Informasi Akuntansi dan Penentuan Product Cost, Pricing dan Standard Variance Analysis pada Warung Benjut - David Tanujaya; Silvia Rostianingsih; Andy Setiabudi (Jurnal Infra, 2015)
Currently, accounting system at Warung Benjut still use manual way to record any part of the existing business processes within the company. Manual transaction recording makes it vulnerable to human error include recording errors, lack of clarity writing or loss of data. The lack of accuracy to calculate the cost of goods sold is also an issue for determining the selling price of the food companies.In addition, the use of food as well be one important factor in maximizing corporate profits. The use of food ingredients to efficiently support the efficiency of the cost incurred by the company. This application was created to support the performance of the company include determining the cost of production, determining the selling price of food, and calculate the efficiency of raw materials used by the company. This application was made and developed with Visual Basic 2010 programming language and MySQL.The results obtained from the application are the calculation of cost of production, accounting journals, reports: the balance sheet, trial balance, stock card, general ledger, accounts payable, accounts receivable, sales reports, purchasing reports, stock reports, profit income, standard variance analysis.